2019
DOI: 10.1002/pssa.201900663
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Magnetic Cobalt and Electrically Conductive Polyaniline‐Filled Three‐Phase Nanocomposite for Microwave Absorption

Abstract: Magnetic cobalt (Co) and electrically conductive polyaniline (PANI)-filled polyurethane (PU) composite (Co@PANI@PU) film is proposed for microwave absorption. This three-phase Co@PANI@PU composite is fabricated through mechanical ball milling of Co microspheres and PANI particles, followed by their casting forming with PU. Prior to that, Co microspheres and conductive PANI are synthesized by ultrasonic-assisted solution reduction and simple oxidation polymerization, respectively. Field-emission scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The diffraction pattern of Co@PANI composites have been found to be similar with that of pure PANI however, the diffraction peak at 46.2° reveal that cobalt ion was anchored on the PANI [JCPDS#5‐727]. XRD results confirmed that the solvothermally synthesised Co@PANI‐600 is in amorphous nature [31–32] . The FT‐IR spectra of polymer nano composite Co@PANI‐600 was depicted in Figure 4.…”
Section: Resultsmentioning
confidence: 83%
“…The diffraction pattern of Co@PANI composites have been found to be similar with that of pure PANI however, the diffraction peak at 46.2° reveal that cobalt ion was anchored on the PANI [JCPDS#5‐727]. XRD results confirmed that the solvothermally synthesised Co@PANI‐600 is in amorphous nature [31–32] . The FT‐IR spectra of polymer nano composite Co@PANI‐600 was depicted in Figure 4.…”
Section: Resultsmentioning
confidence: 83%
“…The microwave absorption frequency of this composite can be adjusted by the ratio of the two fillers, showing an application prospect in the frequency‐adjustable EMI‐absorbing material. [ 162 ]…”
Section: Applicationsmentioning
confidence: 99%
“…[65][66][67][68][69] Due to its importance in radar systems, satellite communication, and other critical applications, MA and EMI shielding research has focused on the X-band (8-12 GHz). [70] Communication technologies, Internet of Things (IoT) devices, and wireless networks that use radio frequency (RF), millimeter wave, and other frequencies are transforming technological advancement. Electronic devices use a variety of frequency bands, including S-band (2-4 GHz), C-band (4-8 GHz), Ku-band (12-18 GHz), Ka-band (26.5-40 GHz), and millimeter-wave bands for specific applications.…”
Section: Introductionmentioning
confidence: 99%